2010
DOI: 10.1007/s00520-010-0827-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of salivary gland hypofunction and xerostomia induced by cancer therapies: prevalence, severity and impact on quality of life

Abstract: Salivary gland hypofunction and xerostomia are induced by radiotherapy in the head and neck region depending on the cumulative radiation dose to the gland tissue. Treatment focus should be on optimized/new approaches to further reduce the dose to the parotids, and particularly submandibular and minor salivary glands, as these glands are major contributors to moistening of oral tissues. Other cancer treatments also induce salivary gland hypofunction, although to a lesser severity, and in the case of chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
316
4
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(346 citation statements)
references
References 197 publications
8
316
4
18
Order By: Relevance
“…Hyposalivation is a common acute and long-term complication of antineoplastic therapies of head and neck. 8,30 In HSCT-treated patients, radiotherapy is likely to be one etiological factor for hyposalivation. 9 Hypofunction of salivary glands depends on the cumulative dose to the gland tissue, and exposure to high total radiation doses (426-36 Gy) leads to a significant reduction of salivary secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyposalivation is a common acute and long-term complication of antineoplastic therapies of head and neck. 8,30 In HSCT-treated patients, radiotherapy is likely to be one etiological factor for hyposalivation. 9 Hypofunction of salivary glands depends on the cumulative dose to the gland tissue, and exposure to high total radiation doses (426-36 Gy) leads to a significant reduction of salivary secretion.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In addition, subjective symptoms of dry mouth (xerostomia), altered taste/vision, eating and speaking problems and sensation of a foreign body in the eye are common and known to have a significant impact on the QoL. 8 In a recent study, objectively determined hyposalivation was found in B50% of patients 6 months post-HSCT. 9 In most cases, stimulated saliva flow returned to normal levels within 2 years, but some patients suffered from persisting hyposalivation.…”
Section: Introductionmentioning
confidence: 99%
“…Xerostomia was the most common long-term toxicity reported in the literature. The prevalence can be high as 93% [2,26,27].…”
Section: Oral Radiation Toxicitymentioning
confidence: 99%
“…Like patients with pSS, these individuals experience a marked decline in quality of life (13,14). Although the ductal cells are still functional and can still generate an osmotic gradient (lumen > interstitium), the acinar cells are highly radiosensitive and represent the only water-permeable portion of the gland.…”
mentioning
confidence: 99%